Niger : Selected Issues and Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
This Selected Issues paper underlies the financial sector developments in Niger. The paper presents an overview of the financial sector of Niger and discusses the recent banking developments. It analyzes the recent trends in key microfinance indicators, and investigates reasons behind Niger's relatively weak growth performance. It uses a growth accounting framework to assess the contribution to growth by factor inputs and total factor productivity (TFP) during 1963-2003. The paper also presents neoclassical growth model estimates of the role of macroeconomic variables and other factors in determining economic growth in Niger.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet